2014
DOI: 10.1007/s00396-014-3408-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polymer microspheres with reactive epoxy group and amino groups as stabilizers for gold nanocolloids with recoverable catalysis

Abstract: Narrow disperse poly(divinylbenzene-co-glycidyl methacrylate) (P(DVB-co-GMA)) microspheres with reactive epoxy group were prepared by distillation precipitation copolymerization of divinylbenzene (DVB) and glycidyl methacrylate (GMA) with benzoyl peroxide (BPO) as initiator in neat acetonitrile. The epoxy group was modified with ethylenediamine (EDA) for transferring to amino group, which was used as a stabilizer for the gold metallic nanocolloids during the in situ reduction of gold chloride trihydrate (HAuCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…3b-e, which demonstrated that the loading capacity of fluoride (C-F group) was successfully incorporated onto the microspheres and enhanced with increasing FSt fraction for polymerization. This was similar to the results for the synthesis of poly(DVB-co-acrylonitrile) microspheres with cyano group [31] and poly(DVB-co-glycidyl methacrylate) with epoxy group [32] via distillation precipitation polymerization. Additionally, all of the FTIR spectra of P(FSt-co-St-co-DVB) microspheres in Fig.…”
Section: Synthesis Of P(fst-co-st-co-dvb) Microspheressupporting
confidence: 86%
“…3b-e, which demonstrated that the loading capacity of fluoride (C-F group) was successfully incorporated onto the microspheres and enhanced with increasing FSt fraction for polymerization. This was similar to the results for the synthesis of poly(DVB-co-acrylonitrile) microspheres with cyano group [31] and poly(DVB-co-glycidyl methacrylate) with epoxy group [32] via distillation precipitation polymerization. Additionally, all of the FTIR spectra of P(FSt-co-St-co-DVB) microspheres in Fig.…”
Section: Synthesis Of P(fst-co-st-co-dvb) Microspheressupporting
confidence: 86%
“…To further understand the interaction nature between the amide groups and AuNPs, XPS of Au 4 f and N 1 s were measured for the as-synthesized microspheres as shown in Figure 5. XPS is an effective method for analyzing the interaction at the interface, in particular for the solid material, which has been extensively used to investigate the interaction between the stabilizer and Au particles [27,28]. Figure 5A showed the XPS spectra of N 1 s for SiO 2 @PMBA microspheres (curve a) and SiO 2 @PMBA@Au microspheres (curve b), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to test the catalytic ability and thermoresponsive property, the reduction of 4-NP to 4-AP with NaBH 4 as the reductant was used as the model reaction for the new nanoreactor. An aqueous solution of 4-NP in the presence of excess NaBH 4 has a distinct UV-vis spectral profile with the maximal absorption at 400 nm, while the maximal absorption of 4-AP aqueous solution in the same condition was at 300 nm [28]. When the catalyst was added into the solution, the yellow color of 4-NP faded gradually together with simultaneous decreasing of the absorption peak at 400 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Poly­(glycidyl methacrylate) (PGMA) microsphere, a polymer advantageous due to easy preparation, active surface for stable immobilization, and easy separation by simple centrifugation after reaction, has been extensively used as a support for noble metals. , Nam et al used amine-functionalized PGMA microsphere as the template to fabricate gold crystals with high catalytic activity in converting 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). Li et al deposited gold nanoparticles (12 ± 3 nm) on the surface of poly­(allylamine hydrochloride)-modified PGMA spheres.…”
Section: Introductionmentioning
confidence: 99%